On retarded differential equations with impulses - Quiroga, Maria Elisa [UNESP]; Taboas, Placido Z. (Springer, 2001)
We are concerned with the effect of impulses in retarded functional differential equations. By using fixed point techniques we prove the existence of periodic solutions of some impulsive equations. For a system of retarded differential equation it is shown that an impulsive self-supporting condition can play the role of a dissipative term in order to assure the existence of a convex bounded positively invariant set.
Keywords: retarded differential equations; impulses; ejectivity; periodic solutions